Palm fatty acid distillate esterification using synthesized heterogeneous sulfonated carbon catalyst from plastic waste: characterization, catalytic efficacy and stability, and fuel properties - Hazmi, Balkis; Rashid, Umer; Kawi, Sibudjing; Wan Mokhtar, Wan Nur Aini; Choong, Thomas Shean Yaw; Moser, Bryan R.; Alsalme, Ali (Elsevier, 2022)
The extensive use of plastics in industries and households contributes to the proliferation of plastic waste (PW) in landfills, the oceans, and the environment, which represents a serious threat to numerous fragile ecosystems. Recycling rates for PW are still low, so solutions to the problem of waste accumulation are urgently needed. We report the transformation of waste polyethylene terephthalate food containers into plastic waste char (PWC) via anaerobic pyrolysis and subsequent conversion to an acidic solid catalyst for conversion of palm fatty acid distillate (PFAD) into biodiesel. Such an approach could provide a promising solution to the environmental issue of PW while simultaneously facilitating production of biofuels. In this study, PW was carbonized at 600 °C to yield a carbon precursor that was subsequently treated with sulfuric acid at three sulfonation ratios (1:10, 1:15 and 1:20) to give a series of solid acid sulfonated carbon catalysts, PWC-SO₃H (a), (b) and (c). The synthesized PWC-SO₃H catalysts were thermally stable up to 375 °C. The deposition of sulfonic acid groups onto the catalytic surface was confirmed by infrared spectroscopy. Surface morphology analysis revealed a mesoporous textural structure with random sulfonate group distribution. Changes in crystallinity for PWC and PWC-SO₃H catalysts were determined by x-ray diffraction spectroscopy and supported by Raman analysis. The catalysts were then evaluated for biodiesel production efficacy via esterification of PFAD with methanol. The PWC-SO₃H (b) catalyst (1:15 impregnation ratio) provided the highest yield of PFAD-derived-biodiesel (96.9%) under the optimum reaction conditions of 5 wt% catalyst at 110 °C for 2 h with a methanol to PFAD molar ratio of 18:1. Recyclability studies revealed that the PWC-SO₃H (b) catalyst was reusable for four consecutive reactions while maintaining high catalytic activity. Lastly, the fuel properties of the resulting PFAD biodiesel were within the limits prescribed in ASTM D6751, the American biodiesel standard.